(untitled) (Confluenţe Bibliologice, 2025)
Brotherliness Teachers of Religion Society in Bessarabia was founded in 1910 in Chisinau. House priesthood aim: uniting all religion teachers from secondary schools and environments to help each other in achieving his duties by the Church and School.